Investigation of Toxin Genes of Clostridium difficile Strains Isolated from Hospitalized Patients with Diarrhoea at Marmara University Hospital - (:unkn) unknown (ANKARA MICROBIOLOGY SOC, 2011)
Toxigenic Clostridium difficile strains cause a spectrum of antibiotic-associated diseases ranging from self-limited diarrhea to severe life-threatening colitis. Pathogenesis primarily involves the action of two important cytotoxins, namely toxin A and toxin B. However, epidemics of C.difficile-associated disease due to the novel, highly virulent strains of C.difficile (binary toxin positive and toxin A variant) have been recognised in hospitals of some countries. The aim of this study was to investigate the toxin gene profiles of C.difficile strains isolated from hospitalized patients with diarrhea. The stool specimens collected from 633 inpatients at Marmara University Hospital, Istanbul, Turkey, between September 2006-March 2008, were included to the study. The presence of C.difficile toxins in the samples has been screened by a commercial enzyme immunoassay kit (ImmunoCard Toxins A&B EIA; Meridian Diagnostics, Belgium). Stool samples were also cultivated on cycloserin-cefoxitin-fructose agar (CCFA; BioMerieux, France) at anaerobic conditions, and the isolates were identified by conventional methods and Rapid ID 32A (BioMerieux, France) system. Toxin production of C.difficile strains isolated from stool cultures have been detected by commercially available Triage C.difficile Panel (Biosite Diagnostics, Italy) and ImmunoCard Toxins A&B EIA (Meridian Diagnostics, Belgium) kits. In-house polymerase chain reaction (PCR) was performed to investigate the presence of genes for toxin A (tcdA), toxin B (tcdB) and binary toxin (cdtA and cdtB). Stool specimens from 50 (7.9%) patients (age range: 2->65 years; mean age: 35.9 +/- 27.6 years; 26 were male) yielded C.difficile in culture. All of 50 isolates were found positive for glutamate dehydrogenase enzyme and 28 (56%) were found positive for toxin A with Triage C.difficile Panel kit. Toxin positivity rate was detected as 4.7% (30/633) with EIA test performed in stool samples directly, however this rate was 5.7% (36/633) in culture filtrates of the isolates (n=50), with the same test. Since EIA test yielded false negative results in six samples, the sensitivity of this test was estimated as 85.7% by means of the detection of toxin in direct stool samples. All of the 36 toxin-producing C.difficile isolates were found positive for toxin A and toxin B genes (tcdA+/tcdB+), however there were neither variant strains (tcdA-/tcdB+) nor binary toxin gene positive isolates among tested bacteria. Our results have also indicated that 77.8% (28/36) of patients who harbored toxigenic C.difficile strains have the history of beta-lactam antibiotic (penicillin, cephalosporin and imipenem) use. It was thought that the data of this study would constitute a database on the toxin gene profiles of C.difficile in hospitalized patients with diarrhea both in our hospital and Turkey. The current data have indicated that for the time being there were no risk for isolates producing new toxin variants or binary toxin, however, continuous monitorization of such C.difficile strains is of crucial importance in order to detect the emergence of those strains and establish necessary control and preventive measures.
Keywords: Clostridium difficile; toxin A; toxin B; binary toxin; Turkey; ANTIBIOTIC-ASSOCIATED DIARRHEA; ADP-RIBOSYLTRANSFERASE; BINARY-TOXIN; UNITED-STATES; INFECTIONS; DISEASE; IDENTIFICATION; EPIDEMIOLOGY; PREVALENCE; DIAGNOSIS